Faculty survey about online teaching during early lockdown period of COVID-19 pandemic in a medical college in central India - Anil Kapoor; Anju Kapoor; Kailash Charokar; Anil Mishra; Manjunath V Motagi; Sahebrao K Sadawarte (Wolters Kluwer Medknow Publications, 2020)
Background: COVID-19 pandemic has led to disruption of onsite teaching of medical students, necessitating faculty to start online teaching at a short notice. This faculty survey was conducted with an aim to identify their perceptions, preparations, and participation in online teaching-learning activities during early lockdown period in our medical college. Materials and Methods: A Google form for online survey using a peer-reviewed 27 item questionnaire was designed and the link was shared with all faculty from Dean's office through WhatsApp group and E-mail. Data gathered were analyzed quantitatively and qualitatively to identify the perceptions, challenges faced, and need for corrective actions. Results: Out of 136 faculty, 108 (79.4%) responded. Majority (93; 88.89%) had put efforts to develop their skills for online teaching after lockdown was imposed. Eighty faculty (74.07%) had taken online classes using online platforms, mainly WhatsApp (77.5%), Zoom (56.25%), and Google classroom (25%). Flexibility and convenience for students and teachers were perceived as most common advantages while missing eye contacts and in-depth discussions were perceived as the most common disadvantages. Teaching and assessing cognitive skills was perceived as most feasible and psychomotor skills as least feasible using online platform. Need for faculty training for online-teaching methodology was strongly expressed; a faculty development program for the same was designed and conducted. Conclusions: Majority of the faculty had put efforts to develop skills for online teaching and started taking online classes, mainly on WhatsApp and Zoom. They strongly perceived need for faculty-development for online teaching methodology; teaching and assessment of cognitive skills was perceived as most feasible as compared to other skills.